Novel Antibacterial Approaches and Therapeutic Strategies - Gustavo A. Niño-Vega; Jorge A. Ortiz-Ramírez; Everardo López-Romero (Antibiotics)
The increase in multidrug-resistant organisms worldwide is a major public health threat driven by antibiotic overuse, horizontal gene transfer (HGT), environmental drivers, and deficient infection control in hospitals. In this article, we discuss these factors and summarize the new drugs and treatment strategies suggested to combat the increasing challenges of multidrug-resistant (MDR) bacteria. New treatments recently developed involve targeting key processes involved in bacterial growth, such as riboswitches and proteolysis, and combination therapies to improve efficacy and minimize adverse effects. It also tackles the challenges of the Gram-negative bacterial outer membrane, stressing that novel strategies are needed to evade permeability barriers, efflux pumps, and resistance mechanisms. Other approaches, including phage therapy, AMPs, and AI in drug discovery, are also discussed as potential alternatives. Finally, this review points out the urgency for continued research and development (R&D), industry–academic partnerships, and financial engines to ensure that MDR microbes do not exceed the value of antibacterial therapies.